OBSERVATIONS ON BIONOMICS OF AEDES ALBOPICTUS (SKUSE) (DIPTERA : CULICIDAE) IN CALCUTTA AREA, WEST BENGAL - PAL, T. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1989)
de Segovia) albopictus is known to be continuously displaced from urban towards rural areas of Calcutta The basic ecological profile of this less studied species is presented in the context of changing landscape pattern in the peripheral areas of the city of Calcutta. Simultaneous occurrence of closely related species, A. albopictus and A. aegypti was noticed in a periurban area of Calcutta. Field and laboratory observations extending on the life history provided an insight into the biology of A. albopictus. The adults spend much of their life at resting places, preferably among bushy vegetation in shaded places. Males form 'swarms during evening over bushes. Females bite mostly at twilight. Male and female take venterto-venter position during mating. Oogenesis is completed by 4 days after blood meal. Eggs are deposited in earthenware containers, natural depressions, discarded cans and domestic water-tubs close to rich vegetation. Larval development from eclosion to pupation is completed as early as 6 days but is retarded when food is inadequate in the breeding medium. Larvae are responsive to stimuli like, sound movement of water and sudden changes of light. Adults emerge mostly at night. Certain co-existence of this primarily sylvicolous species in or near human residence, perhaps indicates its propensity to adapt man-made ecological changes.